Ethnopharmacological study of traditional plants with medicinal properties of kapehe pai (gout) in the Dayak Bakumpai tribe - Raudhatuz Zahra; Muhammad Anshari; Risya Mulyani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Traditional medicine by the community has long been used for medicine and health maintenance and has been inherited from generation to generation. Indonesia is very rich in beneficial plants. This study aims to discover the types of plants and plant parts and how they are processed for kapehe pie. Research Methodology: The method used in this study is descriptive and exploratory with a qualitative approach. Data was collected by asking questions with the help of interview guidelines. The informants of this research are tatamba craftsmen and the Dayak Tribe of Sampirang II Village. The number of respondents was 35, consisting of farmers and homemakers. Result: There are five types of plants used for the treatment of kapehe pai (gout), namely bay leaf (syzgium polyanthum), lemongrass (Cymbopogon citratus), ginger (zingiber officinale), kersen (Muntingia calabura), and garlic (Allium sativum). The most widely used plant is bay leaf allergy (syzgium polyanthum). Leaves are the most frequently used plant organs, which is 57.14% of the total, followed by rhizomes (22.85%), stems (11.42%), and seeds (8.57%). The medicinal plants are processed in two ways, namely by boiling and grinding/pounding, with a percentage value of 91.42% for the boiling technique and 8.57% for the kneaded method. 91% of the therapeutic plants are sourced from the gardens around the house, and the remaining 9% come from market purchases Conclusion: Traditional medicine passed down from generation to generation treats kapehe pai (gout). The most widely used part of the plant is the leaf (57.14%), followed by rhizomes, stems, and seeds. Most medicinal plants are obtained from the gardens around the house (91%), while the rest are purchased from the market. This shows the wealth of local knowledge and the utilization of natural resources in traditional medicine.